Aprendizaje colaborativo en la comprensión de textos escritos en inglés en estudiantes de segundo grado de secundaria en instituciones educativas públicas de Iquitos 2024 - Panduro Saman, Shadya Jessel (2025)
This research aimed to explain the influence of collaborative learning on English reading comprehension among second year high school students in Iquitos in 2023. The study was help in an explanatory research type and field-based with contemporary, and multivariable designs. The population consisted of 3430 students, with a sample of 303 second-grade high school students. Data were collected using a cooperative learning questionnaire and a reading comprehension test. After processing the data, results show the following index: 47.9% of the students were at the "in process" level of reading comprehension, with an average score of 11.5 on a scale of 0 to 20. Regarding the collaborative learning variable, the mean score was 89.9 on a scale of 0 to 100. A linear logistic regression data showed an index of (B) of 0.724. Therefore, the study concludes that collaborative learning significantly influences English reading comprehension.